Preparation method and application of defect state nanometer gallium oxide and 2,5-furan dicarboxylic acid-based polyester

CN117756164BActive Publication Date: 2026-10-23DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311254905.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2026-10-23
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

[0005]针对目前存在的2,5-呋喃二甲酸基聚酯合成所用催化剂催化活性不高、催化效率低、不易调控以及缺乏温和高效的循环利用方法等问题,本发明提供了一种应用于催化2,5-呋喃二甲酸基聚酯合成和原位醇解的缺陷态纳米氧化镓催化剂的制备方法

Benefits of technology

[0063]本申请能产生的有益效果包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117756164B_ABST
    Figure CN117756164B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a defect state nano gallium oxide and 2,5-furan dicarboxylic acid-based polyester, wherein the defect state nano gallium oxide has oxygen vacancy defects; the defect state nano gallium oxide can efficiently catalyze the synthesis of 2,5-furan dicarboxylic acid-based polyester, has the advantages of simple catalyst preparation, high catalytic activity, high selectivity of target products and the like, and can also endow the polyester with the characteristics of inorganic material functionalization by using the functional characteristics such as ultraviolet shielding; meanwhile, the defect state nano gallium oxide is in-situ compounded in the 2,5-furan dicarboxylic acid-based polyester, and in the participation of alcohol compounds, the 2,5-furan dicarboxylic acid-based polyester can be alcoholized into organic small molecules to realize the reuse of waste polyester, so that the true sustainable development and circular economy are realized, and the defect state nano gallium oxide has the advantages of in-situ catalytic alcoholization, high PEF conversion rate, mild alcoholization reaction condition, low catalyst consumption, high efficiency and cleanness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a method for preparing defect-state nano-gallium oxide and 2,5-furandicarboxylic acid-based polyester and its application, belonging to the fields of polymer catalyst technology, chemical production and plastic recycling. Background Technology

[0002] White pollution from discarded plastics poses numerous threats to the ecological environment and human health. With increasing environmental awareness, environmentally friendly bio-based polymers have become a hot topic in research and application development. 2,5-furandicarboxylic acid-based polyester is a novel bio-based polyester material with excellent properties and is considered a substitute for petroleum-derived terephthalic acid-based polyesters.

[0003] However, the synthesis and application of 2,5-furandicarboxylic acid-based polyesters still face some challenges, hindering their further development. Common methods for preparing 2,5-furandicarboxylic acid-based polyesters include direct esterification and transesterification, but current catalysts suffer from limitations such as limited variety, low catalytic activity, low catalytic efficiency, difficulty in control, and easy deactivation, resulting in polyesters with dark color, low performance, and poor quality. Therefore, there is an urgent need to develop novel catalytic systems that can precisely control the defect state density on the surface of defect-state nano-oxides to further regulate the acid sites, achieving stable and efficient catalytic effects while ensuring the high performance of the polyester.

[0004] Meanwhile, the post-treatment of the large quantities of waste polyester is also a major concern. Although 2,5-furandicarboxylic acid polyester originates from renewable resources, it is difficult to degrade under natural conditions and mostly requires external catalysts and harsh environmental conditions to degrade. In the long run, this not only impacts the ecological environment but also wastes resources. Therefore, converting 2,5-furandicarboxylic acid polyester into useful chemicals through chemical recycling, under the catalysis of a catalyst, and realizing the recycling of polyester aligns with the principles of sustainable development and has significant research and application value. However, currently, there is a lack of highly efficient catalytic systems in this field. Typically, both the catalytic synthesis and chemical recycling of polyester processes require certain catalysts. Few reports exist on catalysts that can simultaneously achieve controllable and efficient synthesis of polyester and in-situ chemical degradation of polyester materials. The development of such catalysts could realize a truly green recycling process, which is of great significance for environmental protection. Summary of the Invention

[0005] To address the problems of low catalytic activity, low catalytic efficiency, difficulty in control, and lack of mild and efficient recycling methods in the current synthesis of 2,5-furandicarboxylic acid-based polyesters, this invention provides a method for preparing defect-state nano-gallium oxide catalysts for catalytic synthesis and in-situ alcoholysis of 2,5-furandicarboxylic acid-based polyesters.

[0006] According to a first aspect of this application, a defect-state gallium oxide nanoparticle is provided, wherein the defect-state gallium oxide nanoparticle is γ-gallium oxide with oxygen vacancy defects;

[0007] The defect-state gallium oxide nanoparticles have a particle size of 5–200 nm.

[0008] According to a second aspect of this application, a method for preparing the aforementioned defect-state gallium oxide nanoparticles is provided, the method comprising:

[0009] A mixture containing a gallium compound, an alcohol, and water is reacted, dried, and calcined to obtain the defect-state gallium oxide nanoparticles.

[0010] Optionally, the method for preparing the defective state gallium oxide nanoparticles includes: first, mixing and reacting raw materials containing gallium element compound, alcohol and water to prepare a precursor gel; then, washing and drying the precursor gel, and finally calcining it in a muffle furnace to obtain the defective state gallium oxide nanoparticles.

[0011] Optionally, the molar ratio of the alcohol to the gallium compound is 1:(0.001 to 0.01).

[0012] Optionally, the molar ratio of the alcohol to the gallium compound is any value selected from 1:0.001, 1:0.005, 1:0.01, or a range between any two of the above.

[0013] Optionally, the molar ratio of the alcohol to the water is 1:(0.01 to 5).

[0014] Optionally, the molar ratio of the alcohol to the water is any value selected from 1:0.01, 1:0.05, 1:0.1, 1:0.5, 1:1, 1:2.5, 1:5 or a range between any two of the above.

[0015] Optionally, the gallium compound is selected from at least one of gallium halides, gallium nitrates, gallium carbonates, gallium sulfates, and gallium acetates.

[0016] Optionally, the alcohol is selected from at least one of n-butanol, ethylene glycol, butanediol, propylene glycol, pentanediol, diethylene glycol, and polyethylene glycol.

[0017] Optionally, the calcination temperature is 200–800°C; the calcination time is 2–10 h.

[0018] Optionally, the reaction temperature is 120–220°C, and the mixing reaction time is 0.5–24 h.

[0019] According to a third aspect of this application, a method for synthesizing a 2,5-furandicarboxylic acid-based polyester is provided, comprising the following steps:

[0020] (1) In an inactive atmosphere, a mixture I containing a diol, 2,5-furandicarboxylic acid and catalyst I is subjected to an esterification reaction to obtain a prepolymer;

[0021] (2) The prepolymer was subjected to polycondensation reaction to obtain 2,5-furan dicarboxylic acid polyester;

[0022] Catalyst I is the defect-state gallium oxide nanoparticle described above.

[0023] Optionally, the molar amount of catalyst I is 0.1 to 50‰ of the molar amount of 2,5-furandicarboxylic acid.

[0024] Optionally, the molar amount of catalyst I is any value or a range between any two of the molar amounts of 2,5-furandicarboxylic acid, which are 0.1‰, 0.5‰, 1‰, 10‰, 20‰, 30‰, 40‰, and 50‰.

[0025] Optionally, the molar ratio of the diol to the 2,5-furandicarboxylic acid is 1 to 3:1.

[0026] Optionally, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, isosorbide, 1,4-cyclohexanediol, 1,4-cyclohexanediol, 1,3-cyclobutanediol, and polyethylene glycol.

[0027] Preferably, the diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, and polyethylene glycol.

[0028] Optionally, in step (1), the temperature of the esterification reaction is 100℃~250℃, and the time of the esterification reaction is 5min~8h.

[0029] Optionally, the temperature of the esterification reaction is preferably 100℃~250℃, more preferably 150℃~245℃, and most preferably 180℃~240℃.

[0030] Optionally, the esterification reaction time is preferably 5 min to 5 h; more preferably 30 min to 4 h; and most preferably 1 to 3 h.

[0031] Optionally, the inactive atmosphere is selected from at least one of nitrogen, helium, and argon.

[0032] Optionally, in step (2), the temperature of the polycondensation reaction is 200℃~300℃; the time of the polycondensation reaction is 5min~10h.

[0033] Optionally, the temperature of the polycondensation reaction is selected as 200℃~300℃; more preferably 220℃~290℃; and most preferably 230℃~280℃.

[0034] Optionally, the polycondensation reaction time is preferably 5 min to 10 h; more preferably 1 h to 9 h; and most preferably 3 h to 8 h.

[0035] Optionally, in step (2), the vacuum degree of the polycondensation reaction is 10 to 100 Pa.

[0036] The polycondensation reaction described in this application is carried out under vacuum conditions, that is, the reaction flask is evacuated. The vacuum degree of the reaction is preferably 10-100 Pa; more preferably 20-90 Pa; and most preferably 50-90 Pa.

[0037] According to a fourth aspect of this application, a 2,5-furandicarboxylic acid-based polyester prepared by the above-described synthesis method is provided, wherein the number-average molecular weight of the 2,5-furandicarboxylic acid-based polyester is 20 to 100 kg / mol.

[0038] Optionally, the tensile strength of the 2,5-furandicarboxylic acid-based polyester is 20 to 135 MPa.

[0039] Optionally, the elongation at break of the 2,5-furandicarboxylic acid-based polyester is 5 to 1250%.

[0040] According to a fifth aspect of this application, a method for in-situ alcoholysis of 2,5-furandicarboxylic acid-based polyester is provided, the method comprising:

[0041] Under an inactive atmosphere, a mixture II containing 2,5-furandicarboxylic acid polyester, ethylene glycol, and catalyst II is subjected to a depolymerization reaction to obtain ethylene glycol 2,5-furandicarboxylic acid ester.

[0042] The catalyst II is selected from the defect-state nano-gallium oxide described in claim 1;

[0043] The 2,5-furandicarboxylic acid polyester is selected from the 2,5-furandicarboxylic acid polyester described above.

[0044] Optionally, the application of the defect-state nano-gallium oxide catalyst in the in-situ alcoholysis of 2,5-furandicarboxylic acid-based polyesters includes the following steps:

[0045] (1) Under normal pressure and inert gas protection, without external catalyst, the reactants polyethylene 2,5-furandicarboxylate and ethylene glycol are added to the reactor in sequence, with the mass ratio of 2,5-furandicarboxylate to ethylene glycol being 1:0.5 to 10.

[0046] (2) Heat the reaction system in an oil bath to 40-240°C and maintain for 0.5-10 hours;

[0047] (3) After the reaction is complete, the reactor is cooled to room temperature in an ice-water bath, filtered, and the filter cake is washed, dried and weighed to calculate the conversion rate of 2,5-furandicarboxylic acid polyester.

[0048] (4) The filtered solution was diluted to volume with deionized water in a volumetric flask. The 2,5-furandicarboxylic acid ethylene glycol ester was determined by quantitative analysis using liquid chromatography-mass spectrometry. Subsequently, most of the deionized water was removed from the solution by rotary evaporation, followed by cooling and crystallization and filtration. The solid was washed with water and dried to obtain pure 2,5-furandicarboxylic acid ethylene glycol ester.

[0049] In step (1), the 2,5-furandicarboxylic acid polyester is preferably at least one of the 2,5-furandicarboxylic acid polyesters synthesized by the above-described catalytic method for synthesizing 2,5-furandicarboxylic acid polyester.

[0050] In step (1), the alcohol is selected from ROH, diols, or triols;

[0051] Wherein, R is selected from C 1~5 The alkyl group; preferably, the ROH is selected from at least one of methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, tertiary butanol, 1-pentanol, 2-pentanol, 3-pentanol, 2-methyl-1-butanol, 2-methyl-2-butanol, 3-methyl-2-butanol, 3-methyl-1-butanol and 2,2-dimethyl-1-propanol.

[0052] The diol is selected from C 2~6 The diol is selected from at least one of ethylene glycol, 1,3-propanediol, and 1,5-pentanediol.

[0053] The triol is selected from C 3~6 The triol; preferably, the triol is selected from at least one of glycerol, 1,2,3-butanetriol, 1,2,5-pentanetriol, and 1,2,6-hexanetriol.

[0054] Optionally, the molar amount of catalyst II is 0.1 to 50‰ of the molar amount of 2,5-furandicarboxylic acid polyester.

[0055] Optionally, the mass ratio of the 2,5-furandicarboxylic acid polyester to ethylene glycol is 1:0.5 to 10.

[0056] Optionally, the mass ratio of the 2,5-furandicarboxylic acid-based polyester to ethylene glycol is selected from any value of 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, or any value between any two of the above.

[0057] Optionally, the temperature of the depolymerization reaction is 40–240°C, and the time of the depolymerization reaction is 0.5–10 h.

[0058] Optionally, the temperature of the depolymerization reaction is selected from any value of 40℃, 50℃, 60℃, 70℃, 80℃, 90℃, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, or a range between any two of the above.

[0059] Optionally, the depolymerization reaction time is selected from any value of 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or a range between any two of the above.

[0060] In this application, polyethylene 2,5-furandicarboxylate is abbreviated as "PEF"; ethylene glycol is abbreviated as "EG"; and polyethylene 2,5-furandicarboxylate is abbreviated as "BHEF".

[0061] In this application, "C1-C6" in "C1-6 alkyl" refers to the number of carbon atoms, and "alkyl" in "C1-6 alkyl" refers to the group obtained by losing one H atom in an alkane molecule.

[0062] In this application, the defective state gallium oxide nanoparticles possess oxygen vacancy defects. These defective state gallium oxide nanoparticles can efficiently catalyze the synthesis of 2,5-furandicarboxylic acid-based polyesters, possessing advantages such as simple catalyst preparation, high catalytic activity, and high selectivity for target products. Furthermore, utilizing its own ultraviolet shielding and other functional characteristics, it can also endow the inorganic polyester material with functional properties. Simultaneously, the defective state gallium oxide nanoparticles are in situ composited in 2,5-furandicarboxylic acid-based polyesters. With the participation of alcohol compounds, the 2,5-furandicarboxylic acid-based polyesters can be rapidly alcoholyzed into small organic molecules, realizing the reuse of waste polyesters, thereby achieving true sustainable development and a circular economy. It has the advantages of in-situ catalytic alcoholysis, high PEF conversion rate, mild alcoholysis reaction conditions, low catalyst dosage, high efficiency, and cleanliness.

[0063] The beneficial effects that this application can produce include:

[0064] 1) The defective state nano-gallium oxide provided in this application is used as a catalyst for the preparation of 2,5-furandicarboxylic acid-based polyester. It is not only simple and safe to prepare, but also has high catalytic activity, good selectivity, high catalytic efficiency and good stability. It can also obtain high molecular weight 2,5-furandicarboxylic acid-based polyester.

[0065] 2) This application further regulates the Lewis acid sites on the surface of defective nano-oxides by precisely controlling the defect state density, thereby achieving a stable and efficient catalytic effect while ensuring the high performance of the polyester.

[0066] 3) Compared with conventional catalyst-catalyzed depolymerization methods of polyester, the defect-state nano-gallium oxide catalyst provided in this application can be applied in situ in the polyester alcoholysis reaction. It requires less dosage, and its catalytic activity and efficiency are significantly improved, making the reaction conditions milder and reducing energy consumption. The reaction system can avoid environmental pollution and PEF dissolution by additional organic solvents, simplifying the operation process.

[0067] 4) This application can use the same catalyst to achieve the polymerization process to obtain 2,5-furandicarboxylic acid-based polyester materials. At the same time, by controlling the reaction conditions, the obtained 2,5-furandicarboxylic acid-based polyester materials can be depolymerized into useful small molecules, realizing a true recycling process. Attached Figure Description

[0068] Figure 1 Electron micrograph of the defect-state gallium oxide nanoparticles obtained in Example 1 of this application; scale bar is 20 nm.

[0069] Figure 2 Electron paramagnetic resonance spectrum of the defect-state gallium oxide nanoparticles obtained in Example 1 of this application.

[0070] Figure 3 The HN3-TPD spectrum of the defect-state gallium oxide nanoparticles obtained in Example 1 of this application is shown.

[0071] Figure 4 The NMR spectra are those of the polymers prepared in Examples 1-3 of this application.

[0072] Figure 5 The ultraviolet light transmittance curves of the PEFs prepared in Examples 1 to 3 of this application are shown.

[0073] Figure 6 This is the NMR spectrum of the alcoholysis product in Example 7.

[0074] Figure 7 This is the mass spectrum of the alcoholysis product in Example 7. Detailed Implementation

[0075] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0076] Unless otherwise specified, the 2,5-furandicarboxylic acid-based polyester and catalyst in the embodiments of this application are all self-made, and the alcohol is purchased commercially.

[0077] Furan dicarboxylic acid was prepared according to the method in Example 1 of patent CN108558800A.

[0078] In the embodiments of this application, a gel permeation chromatography instrument (Waters 1515 Isocratic HPLC Pump) was used to measure molecular weight. Tensile strength and elongation at break were measured using an Instron electronic universal testing machine (Instron-1121). Tensile tests were performed at 25°C using the Instron-1121 machine according to ASTM D638 requirements. The tensile speed was 2 mm / min. Dumbbell-shaped samples with a width of 3.18 mm and a thickness of 3.2 mm were prepared by injection molding, and the tensile strength and elongation at break of the samples were obtained. The composition and purity of the alcoholysis products were obtained using liquid chromatography-mass spectrometry (Q-TOF 6540).

[0079] The degradation rate of 2,5-furandicarboxylic acid-based polyester is calculated according to formula (1), where A is the initial mass of reactant PEF and B is the mass of undegraded 2,5-furandicarboxylic acid-based polyester:

[0080]

[0081] The yield of ethylene glycol 2,5-furandicarboxylate was calculated according to formula (2):

[0082]

[0083] In this invention, polyethylene 2,5-furandicarboxylate is abbreviated as "PEF"; ethylene glycol is abbreviated as "EG"; polyethylene 2,5-furandicarboxylate is abbreviated as "BHEF"; and "PET" is polyethylene terephthalate.

[0084] Preparation Example 1: Preparation of Defect-State Gallium Oxide Nanoparticles

[0085] Defect-state gallium oxide: Under nitrogen protection, 1 g of anhydrous gallium chloride was added to 166.95 g of ethylene glycol, heated to reflux, and 0.6 g of water was added hot. The mixture was then refluxed and reacted (e.g., a mixed reaction) for a certain time to obtain a precursor. After natural cooling, the precursor gel was centrifuged, washed with anhydrous ethanol, and dried. The dried precursor powder was then calcined in a muffle furnace at high temperature for at least 2 hours. The molar ratio of alcohol to gallium oxide to water was 1:0.2% to 1.2%. The particle size of the defect-state gallium oxide nanoparticles was 6–8 nm.

[0086] The reaction conditions were as follows: the reaction temperature was 200℃; the reaction time was 6 hours; the calcination temperature in the muffle furnace was 450℃; and the calcination time in the muffle furnace was 4 hours.

[0087] Figure 1 Electron microscopy images of the defect-state gallium oxide nanoparticles obtained in Example 1 of this application; scale bar is 20 nm. From Figure 1 As can be seen from the data, the defect-state gallium oxide nanoparticles prepared are nanoscale.

[0088] Figure 2 Electron paramagnetic resonance (EPR) spectra of the defect-state gallium oxide nanoparticles obtained in Example 1 of this application. From... Figure 2 As can be seen, the prepared defect-state gallium oxide nanoparticles exhibit significant oxygen vacancy trapping electrons (O... - The presence of a signal peak (g = 2.004) indicates that the prepared defect-state gallium oxide nanoparticles have oxygen vacancy defects on their surface.

[0089] Figure 3 The HN3-TPD spectrum of the defect-state gallium oxide nanoparticles obtained in Example 1 of this application is shown. Figure 3 From this, we can deduce the surface acid sites and surface acid content of the prepared defect-state gallium oxide nanoparticles.

[0090] I. Defect-state gallium oxide nano-catalyzed polymerization of 2,5-furandicarboxylic acid-based polyester

[0091] Example 1

[0092] (1) 1.0 mol of 2,5-furandicarboxylic acid and 1.7 mol of ethylene glycol were added to a reaction flask. The defective state gallium oxide nanoparticles prepared in Example 1 were used as catalysts, accounting for 0.05% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection at 210 °C for 2 h to generate a prepolymer.

[0093] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 240 °C for 4 h to obtain polyethylene 2,5-furandicarboxylate (PEF1). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0094] Example 2

[0095] (1) 1.0 mol of 2,5-furandicarboxylic acid and 1.7 mol of ethylene glycol were added to a reaction flask. The defective state gallium oxide nanoparticles prepared in Example 1 were used as catalysts, accounting for 0.1% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection at 210 °C for 2 h to generate a prepolymer.

[0096] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 240 °C for 4 h to obtain polyethylene 2,5-furandicarboxylate (PEF2). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0097] Example 3

[0098] (1) 1.0 mol of 2,5-furandicarboxylic acid and 1.7 mol of ethylene glycol were added to a reaction flask. The defective state gallium oxide nanoparticles prepared in Example 1 were used as catalysts, accounting for 0.2% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection at 210 °C for 2 h to generate a prepolymer.

[0099] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 240 °C for 4 h to obtain polyethylene 2,5-furandicarboxylate (PEF3). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0100] Figure 4 The images show the NMR spectra of the polymers prepared in Examples 1-3 of this application. It can be seen that they are all PEF.

[0101] Figure 5 The ultraviolet transmittance curves of the PEFs prepared in Examples 1-3 of this application are shown. It can be seen that in the wavelength range of 320-400 nm, their ultraviolet shielding performance increases with the increase of the amount of defect-state gallium oxide.

[0102] Example 4

[0103] (1) 1.0 mol of 2,5-furandicarboxylic acid and 3 mol of 1,4-butanediol were added to a reaction flask. The defective state gallium oxide nanoparticles prepared in Example 1 were used as catalysts, accounting for 0.1% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection at 220°C for 2 h to generate a prepolymer.

[0104] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 230 °C for 3 h to obtain polybutylene 2,5-furandicarboxylate (PBF1). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0105] Example 5

[0106] (1) 1.0 mol of 2,5-furandicarboxylic acid and 8 mol of 1,3-propanediol were added to a reaction flask. The defective state gallium oxide nanoparticles prepared in Example 1 were used as catalysts, accounting for 0.1% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection and stirred at 180°C for 3 h to generate a prepolymer.

[0107] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 220°C for 2 h to obtain poly(propylene glycol 2,5-furandicarboxylate) (PTF1). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0108] Comparative Example 1

[0109] (1) 1.0 mol of 2,5-furandicarboxylic acid and 1.7 mol of ethylene glycol were added to a reaction flask, with tetrabutyl titanate as a catalyst, accounting for 0.1% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection at 220°C for 2 h with stirring to generate a prepolymer.

[0110] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 240 °C for 4 h to obtain polyethylene 2,5-furandicarboxylate (PEF4). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0111] Comparative Example 2

[0112] (1) 1.0 mol of 2,5-furandicarboxylic acid and 3 mol of 1,4-butanediol were added to a reaction flask, with tetrabutyl titanate as a catalyst, accounting for 0.1% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection at 220°C for 2 h to generate a prepolymer.

[0113] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 230 °C for 3 h to obtain polybutylene 2,5-furandicarboxylate (PBF2). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0114] Comparative Example 3

[0115] (1) 1.0 mol of 2,5-furandicarboxylic acid and 8 mol of 1,3-propanediol were added to a reaction flask, with tetrabutyl titanate as a catalyst, accounting for 0.1% of the molar fraction of 2,5-furandicarboxylic acid. The reaction was carried out under nitrogen protection and stirred at 180°C for 3 h to generate a prepolymer.

[0116] (2) The prepolymer was evacuated to 0.090 MPa and stirred at 220°C for 2 h to obtain poly(propylene 2,5-furandicarboxylate) (PTF2). The molecular weight (Mn) and molecular weight distribution (PDI) of the obtained polymer were determined by gel permeation chromatography (GPC). The obtained sample was then pulverized and subjected to injection molding and mechanical property tests. The results are shown in Table 1.

[0117] Table 1

[0118]

[0119] Table 1 compares the catalytic activities of defective gallium oxide nanoparticles and tetrabutyl titanate in the synthesis of 2,5-furandicarboxylic acid polyesters. Under the same catalyst dosage, the 2,5-furandicarboxylic acid polyester synthesized by defective gallium oxide nanoparticles exhibits a higher molecular weight and better mechanical properties than that synthesized by tetrabutyl titanate.

[0120] II. Defect-state gallium oxide nanocatalyzed in-situ alcoholysis of 2,5-furandicarboxylic acid polyester

[0121] The polyethylene 2,5-furandicarboxylate (PEF) in Examples 6-12 was selected from the PEF prepared in Example 3.

[0122] The PEF and PET in Comparative Examples 3-5 were all purchased commercially.

[0123] Example 6

[0124] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:4. The reaction system was heated to 210°C in an oil bath and maintained for 1 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure ethylene glycol 2,5-furandicarboxylate (BHEF). The conversion rate of PEF and the yield of BHEF were calculated, and the results are shown in Table 2.

[0125] Example 7

[0126] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:4. The reaction system was heated to 190°C in an oil bath and maintained for 1 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure BHEF. The PEF conversion rate and BHEF yield were calculated, and the results are shown in Table 2.

[0127] Figure 6 This is the NMR spectrum of the alcoholysis product from Example 7. It can be seen that the alcoholysis product is a small molecule.

[0128] Figure 7 This is the mass spectrum of the alcoholysis product in Example 7. It can be seen that the alcoholysis product is a mixture of small molecule ethylene glycol 2,5-furandicarboxylate, a small amount of ethylene glycol 2,5-furandicarboxylate dimer, ethylene glycol, and diethylene glycol.

[0129] Example 8

[0130] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:4. The reaction system was heated to 170°C in an oil bath and maintained for 1 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure BHEF. The PEF conversion rate and BHEF yield were calculated, and the results are shown in Table 2.

[0131] Example 9

[0132] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:4. The reaction system was heated to 190°C in an oil bath and maintained for 0.5 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure BHEF. The PEF conversion rate and BHEF yield were calculated, and the results are shown in Table 2.

[0133] Example 10

[0134] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:4. The reaction system was heated to 190°C in an oil bath and maintained for 2 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure BHEF. The PEF conversion rate and BHEF yield were calculated, and the results are shown in Table 2.

[0135] Example 11

[0136] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:2. The reaction system was heated to 190°C in an oil bath and maintained for 1 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure BHEF. The PEF conversion rate and BHEF yield were calculated, and the results are shown in Table 2.

[0137] Example 12

[0138] Under normal pressure and a nitrogen atmosphere, PEF and ethylene glycol were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The defect-state gallium oxide nanoparticles prepared in Example 1 were used as the catalyst, with the catalyst amount being 0.1% of the molar fraction of PEF. The mass of PEF was 2 g, and the mass ratio of PEF to ethylene glycol was 1:8. The reaction system was heated to 190°C in an oil bath and maintained for 1 h. After the reaction, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was then filtered, washed, and extracted to obtain pure BHEF. The PEF conversion rate and BHEF yield were calculated, and the results are shown in Table 2.

[0139] Comparative Example 3

[0140] Under normal pressure and a nitrogen atmosphere, PEF, ethylene glycol, and DES (urea / zinc acetate, 4:1) were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The mass of PEF was 2g, the mass ratio of PEF to ethylene glycol was 1:4, and DES (urea / zinc acetate, 4:1) accounted for 5% of the mass of PEF. The reaction system was heated to 190℃ in an oil bath and maintained for 1h. After the reaction was completed, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was filtered, washed, and extracted to obtain pure BHEF. The conversion rate of PEF and the yield of BHEF were calculated, and the results are shown in Table 2.

[0141] Comparative Example 4

[0142] Under normal pressure and a nitrogen atmosphere, reactants PEF, ethylene glycol, and DES (urea / zinc acetate, 4:1) were sequentially added to a reaction flask equipped with a stirrer and a thermometer. The mass of PEF was 2 g, the mass ratio of PEF to ethylene glycol was 1:2, and DES (urea / zinc acetate, 4:1) accounted for 5% of the mass of PEF. The reaction system was heated to 210°C in an oil bath and maintained for 1 h. After the reaction was completed, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was filtered, washed, and extracted to obtain pure BHEF. The conversion rate of PEF and the yield of BHEF were calculated, and the results are shown in Table 2.

[0143] Comparative Example 5

[0144] PET, ethylene glycol, and ZIF-8 were sequentially added to a reaction flask equipped with a stirrer and thermometer under a nitrogen atmosphere of 0.1 MPa. The mass of PET was 2 g, the mass ratio of PET to ethylene glycol was 1:5, and ZIF-8 accounted for 0.4% of the mass of PET. The reaction system was heated to 210 °C in an oil bath and maintained for 0.5 h. After the reaction was completed, the reaction vessel was cooled to room temperature in an ice-water bath. The reaction solution was filtered, washed, and extracted to obtain pure BHET. The conversion rate of PET and the yield of BHET were calculated, and the results are shown in Table 2.

[0145] Table 2

[0146]

[0147]

[0148] As can be seen from Table 2 above, defect-state nano-gallium oxide exhibits high catalytic activity in the in-situ alcoholysis of polyester under mild conditions. The polyester conversion rate and monomer yield under different conditions are significantly higher than those of the alcoholysis results of the added alcoholysis catalysts DES and ZIF-8.

[0149] The above description is merely a few embodiments of this application and is not intended to limit this application in any way. Although this application discloses preferred embodiments as described above, it is not intended to limit this application. Any changes or modifications made by those skilled in the art without departing from the scope of the technical solution of this application using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A defect-state gallium oxide nanoparticle, characterized in that, The defective state gallium oxide nanoparticles are γ-gallium oxide with oxygen vacancy defects; The defect-state gallium oxide nanoparticles have a particle size of 5~200 nm; The defective state nano-gallium oxide is prepared by reacting, drying, and calcining a mixture containing gallium compounds, alcohols, and water.

2. The defect-state gallium oxide nanoparticle according to claim 1, characterized in that, The molar ratio of the alcohol to the gallium compound is 1:(0.001~0.01).

3. The defect-state gallium oxide nanoparticle according to claim 1, characterized in that, The molar ratio of the alcohol to the water is 1:(0.01~5).

4. The defect-state gallium oxide nanoparticle according to claim 1, characterized in that, The gallium compound is selected from at least one of gallium halides, gallium nitrates, gallium carbonates, gallium sulfates, and gallium acetates.

5. The defect-state gallium oxide nanoparticle according to claim 1, characterized in that, The alcohol is selected from at least one of n-butanol, ethylene glycol, butanediol, propylene glycol, pentanediol, diethylene glycol, and polyethylene glycol.

6. The defect-state gallium oxide nanoparticle according to claim 1, characterized in that, The calcination temperature is 200~800 ℃; the calcination time is 2~10 h.

7. The defect-state gallium oxide nanoparticle according to claim 1, characterized in that, The reaction temperature is 120~220 ℃, and the reaction time is 0.5~24 h.

8. A method for synthesizing a 2,5-furandicarboxylic acid-based polyester, characterized in that, Includes the following steps: (1) In an inactive atmosphere, a mixture I containing a diol, 2,5-furandicarboxylic acid and catalyst I is subjected to an esterification reaction to obtain a prepolymer; (2) The prepolymer is subjected to polycondensation reaction to obtain 2,5-furandicarboxylic acid polyester; The catalyst I is selected from the defect-state nano-gallium oxide described in claim 1.

9. The synthesis method according to claim 8, characterized in that, The molar amount of catalyst I is 0.1 to 50‰ of the molar amount of 2,5-furandicarboxylic acid.

10. The synthesis method according to claim 8, characterized in that, The molar ratio of the diol to the 2,5-furandicarboxylic acid is 1 to 3:

1.

11. The synthesis method according to claim 8, characterized in that, The diol is selected from at least one of ethylene glycol, 1,3-propanediol, 1,2-propanediol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, isosorbide, 1,4-cyclohexanediol, 1,4-cyclohexanediol, 1,3-cyclobutanediol, and polyethylene glycol.

12. The synthesis method according to claim 8, characterized in that, In step (1), the temperature of the esterification reaction is 100 ℃~250 ℃, and the time of the esterification reaction is 5 min~8 h.

13. The synthesis method according to claim 8, characterized in that, The inactive atmosphere is selected from at least one of nitrogen, helium, and argon.

14. The synthesis method according to claim 8, characterized in that, In step (2), the temperature of the polycondensation reaction is 200 ℃~300 ℃; the time of the polycondensation reaction is 5 min~10 h.

15. The synthesis method according to claim 8, characterized in that, In step (2), the vacuum degree of the polycondensation reaction is 10~100 Pa.

16. The 2,5-furandicarboxylic acid-based polyester prepared by the synthesis method according to any one of claims 8 to 15, characterized in that, The number-average molecular weight of the 2,5-furan dicarboxylic acid-based polyester is 20~100 kg / mol.

17. The 2,5-furandicarboxylic acid-based polyester prepared by the synthesis method according to any one of claims 8 to 15, characterized in that, The tensile strength of the 2,5-furan dicarboxylic acid-based polyester is 20~135 MPa.

18. The 2,5-furandicarboxylic acid-based polyester prepared by the synthesis method according to any one of claims 8 to 15, characterized in that, The elongation at break of the 2,5-furan dicarboxylic acid-based polyester is 5 to 1250%.

19. A method for in-situ alcoholysis of 2,5-furandicarboxylic acid-based polyester, characterized in that, The method includes: Under an inactive atmosphere, a mixture II containing 2,5-furandicarboxylic acid polyester, ethylene glycol, and catalyst II is subjected to a depolymerization reaction to obtain ethylene glycol 2,5-furandicarboxylic acid ester. The catalyst II is selected from the defect-state nano-gallium oxide described in claim 1; The 2,5-furandicarboxylic acid polyester is selected from the 2,5-furandicarboxylic acid polyester of claim 16.

20. The method according to claim 19, characterized in that, The molar amount of catalyst II is 0.1 to 50‰ of the molar amount of 2,5-furandicarboxylic acid polyester.

21. The method according to claim 19, characterized in that, The mass ratio of the 2,5-furan dicarboxylic acid polyester to ethylene glycol is 1:0.5~10.

22. The method according to claim 19, characterized in that... The depolymerization reaction is carried out at a temperature of 40~240 ℃ and for a time of 0.5~10 h.

Citation Information

Patent Citations

  • Industrial preparation method of low-cost 2,5-furan dicarboxylic acid

    CN108558800A